2014
DOI: 10.1055/s-0034-1387719
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Mitiglinide Combined with Dapagliflozin in Streptozotocin-nicotinamide-induced Type 2 Diabetic Rats and in Zucker Fatty Rats

Abstract: The efficacy of the combination of the rapid-acting insulin secretagogue mitiglinide and the sodium-glucose cotransporter 2 (SGLT2) inhibitor dapagliflozin was explored in streptozotocin-nicotinamide-induced type 2 diabetic (STZ-NA) rats and in Zucker fatty (ZF) rats. The STZ-NA rats were prepared at 8 weeks of age. At 9 weeks of age, the combination study was conducted by oral glucose tolerance test (OGTT). At 13 weeks of age, ZF rats were dosed orally with dapagliflozin once daily up to the 22(nd) day. At da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…Combining mitiglinide and canagliflozin induced stronger hypoglycaemic effects, and less insulin secretion than mitiglinide alone did. The hypoglycaemic effect was similar to that induced by dapagliflozin . These findings reflected both the rapid insulin secretion by mitiglinide and SGLT2 inhibition by canagliflozin.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…Combining mitiglinide and canagliflozin induced stronger hypoglycaemic effects, and less insulin secretion than mitiglinide alone did. The hypoglycaemic effect was similar to that induced by dapagliflozin . These findings reflected both the rapid insulin secretion by mitiglinide and SGLT2 inhibition by canagliflozin.…”
Section: Discussionsupporting
confidence: 61%
“…We previously confirmed the additive hypoglycaemic effects of the mitiglinide and DPP‐IV or SGLT2 inhibitor combination. In contrast to the enhancement of activity alone, we showed that these combinations reduced side effects of each antidiabetic drug by decreasing their dose requirements while maintaining the hypoglycaemic effects . Mitiglinide showed an additive hypoglycaemic effect in combination with the four antidiabetic drugs used in this study.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations